Cognitive Achievement Paradox in High School Physics: Discrepancy Between Test Performance and Conceptual Understanding - Hermansyah Hermansyah; Syarif Fitriyanto; Sri Hartini; Cici Aprina; Armansyah Putra (Pendidikan Fisika Universitas Nurul Huda, 2026)
This study investigated the Cognitive Achievement Paradox in high school physics learning under conditions where high grades are accompanied by shallow conceptual understanding. A convergent-parallel mixed-methods design involved 48 11th-grade students at a public high school in Sumbawa. Data were collected through a concept test on Heat and Temperature, structured interviews, and classroom observations. Quantitative analysis using SPSS 26 showed a class mean of 89.81 (SD = 8.74), 95.8% achieved the KKM (≥75), and Shapiro–Wilk showed non-normality (W = 0.897, p < .001). However, qualitative findings revealed an inability to contextualize thermal phenomena, a reliance on memorization, and inadequate integration of simulation media. Results confirmed that calculation-based assessment systematically overestimates true understanding, threatening construct validity and scientific literacy. A quasi-experimental study testing the Simulation-Anchored Contextual Assessment model based on PhET simulations as an embedded formative assessment tool is recommended